Reversing the effects of evolutionary prey naiveté through controlled predator exposure. Issue 7 (14th May 2019) - Ross, Alexandra K.; Letnic, Mike; Blumstein, Daniel T.; Moseby, Katherine E.
Abstract: Inappropriate anti‐predator responses (naiveté) towards introduced predators is a key factor contributing to the extinction and endangerment of prey species world‐wide and the failure of wildlife reintroductions. Here, we test the idea that success of reintroduction can be improved by exposing a predator naïve prey species to introduced predators under controlled conditions (in situ predation) prior to reintroduction, such that prey adopt increased wary behaviours to aid in survival. We exposed a population of a naïve marsupial, the greater bilby ( Macrotis lagotis ), to a controlled number of introduced predators (feral cats, Felis catus ) for 2 years within a large fenced paddock and then compared the pre‐release behaviour and post‐translocation survival of predator‐exposed and predator‐naïve bilbies over 40 days. Behavioural assays conducted in a small pen prior to reintroduction suggested that predator‐exposed bilbies were warier as they spent less time moving and more time in cover than predator naïve bilbies. After translocation, predator‐exposed bilbies were more likely to survive to 40 days and were less likely to be preyed upon by cats than predator‐free bilbies. Synthesis and applications . Naiveté towards predators is a major problem thwarting successful reintroductions world‐wide. Our study demonstrates that exposure to predators under controlled conditions can increase survival of reintroduced prey and is a promising approach to overcome the problem of naiveté towards introduced predators and the global problem of prey naiveté. Future conservation of naïve prey species may depend on such training methods prior to releasing into areas where predators are present. Abstract : Naiveté towards predators is a major problem thwarting successful reintroductions world‐wide. Our study demonstrates that exposure to predators under controlled conditions can increase survival of reintroduced prey and is a promising approach to overcome the problem of naiveté towards introduced predators and the global problem of prey naiveté. Future conservation of naïve prey species may depend on such training methods prior to releasing into areas where predators are present.